Children’s Diets and Planetary Health: A Study in Wroclaw, Poland, and Sydney, Australia - Agnieszka Orkusz; Diana Bogueva (Foods, 2024)
Meals served to children should not only satisfy hunger and taste preferences but also be nutritionally adequate. Nutrition in early childhood is critical, as children spend a significant portion of their day in kindergarten or preschool, making these settings key contributors to their overall dietary intake. With the rising prevalence of nutrition-related health conditions among children, early interventions are essential for developing and establishing lifelong healthy eating habits. This study assessed the nutritional value and quality of children’s diets in two distinct settings: kindergartens in Wroclaw, Poland, and preschools in Sydney, Australia, evaluating their alignment with the planetary health diet. The research analysed 10-day menu cycles from five kindergartens in Wroclaw and the contents of lunchboxes from five preschools in Sydney’s Upper North Shore area. A total of 100 menus were reviewed in Poland, while 100 children’s lunchboxes were assessed in Australia. Different analytical methods were employed: the Diet 6D software program for the Polish menus and the Food Consumption Score for the Australian lunchboxes. Both methods revealed dietary imbalances, such as excessive intake of protein, vitamin A, salt, and sugar, alongside deficiencies in calcium, vitamin C, and vitamin D. The study concluded that children’s diets should adhere to nutritional guidelines, meeting both Polish and Australian standards, and align with the principles of the planetary health diet. To achieve this, nutritional education is essential for kindergarten staff in Poland, while targeted educational interventions are needed for parents and children in both Poland and Australia, promoting health and environmental sustainability through better nutrition.